Study on the susceptibility of Enterococcus faecalis from infectious processes to ciprofloxacin and vancomycin - Genaro, A. [UNESP]; Cunha, M. L. R. S. [UNESP]; Lopes, C. A. M. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Enterococcus faecalis is considered a pathogen responsible for hospital infections and, due to its frequent multi-resistant profile, has caused preoccupations among many medical authorities. The objective of this study was to determine the antimicrobial susceptibility of 74 strains isolated from blood cultures and purulent secretions to vancomycin and ciprofloxacin through the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) by using the Microdilution test. The results showed a greater efficacy of vancomycin compared to ciprofloxacin (98.6% of the strains were inhibited by vancomycin at lower concentrations: 0.06 - 1 µg/ml). However, in the MBC analysis 73% of the strains showed a MBC of vancomycin only at high concentrations (equal to or higher than 64 µg/ml). For ciprofloxacin, the strains showed a broad sensitivity with MICs and MBCs distributed along all the MIC classes. Results also revealed a probability that some strains are tolerant to vancomycin, which indicates the need of other tests to confirm this characteristic.
Keywords: Enterococcus faecalis; vancomycin; ciprofloxacin; resistance; spontaneous mutation